Suppression of matrix metalloproteinase-9 production from neutrophils by a macrolide antibiotic, roxithromycin, in vitro - Ken-Ichi Kanai; Kazuhito Asano; Tadashi Hisamitsu; Harumi Suzaki (Mediators of Inflammation)
BACKGROUND: Macrolide antibiotics such as erythromycin and roxithromycin (RXM) have an anti-inflammatory effect that may account for their clinical benefit in the treatment of chronic airway inflammatory diseases. However, the precise mechanism of this anti-inflammatory effect is not well understood.